Analisis Yuridis Autentisitas Akta Notaris Yang Dipalsukan - Eko Adi Santoso; FX Joko Priyono (Notarius, 2023)
AbstractThe free will of man causes often problematic problems in the practice of notary positions. The difficulty of knowing and understanding the free will of man causes a variety of issues concerning the falsification of deed notaries. The purpose of this study is to analyze the authenticity of the falsified notarial deed and notary responsibility for the falsified deed. This research method uses normative juridical research method with legal material collection techniques through positive legal inventory, legal principles and doctrines, legal findings in cases in concreto or court decisions. The conclusion of this study is the basis for testing the authenticity of the falsified notaries deed is to understand the forms of deed and the function of notarial deed. While the legal implications of the falsified notarial deed have an impact on the object of the deed's product and the subject, especially notary liability. The implications for the product object of the deed result in it being cancelable, null and void, having no legal force, invalidity or legal force to the extent of the deed under hand. Notary liability for falsified deed can be ensnared in civil, criminal, and other sanctions.Keywords:  notary public; act authenticity; forgeryAbstrakKehendak bebas yang dimiliki manusia menyebabkan sering kali terjadi problematika dalam praktek jabatan notaris. Sulitnya mengetahui dan memahami kehendak bebas manusia menyebabkan berbagai persoalan menyangkut pemalsuan akta notaris. Tujuan penelitian ini adalah menganalisis dasar autentisitas akta notaris yang dipalsukan dan pertanggungjawaban notaris terhadap akta yang dipalsukan. Metode Penelitian ini menggunakan metode penelitian yuridis normatif dengan teknik pengumpulan bahan hukum melalui inventarisasi hukum positif, asas-asas dan doktrin hukum, penemuan hukum dalam perkara in concreto atau putusan pengadilan. Kesimpulan penelitian ini adalah landasan untuk menguji autentisitas akta notaries yang dipalsukan adalah dengan memahami bentuk-bentuk akta dan fungsi akta notaris. Sedangkan implikasi hukum terhadap akta notaris yang dipalsukan berdampak terhadap objek produk akta dan subjek terutama pertanggungjawaban notaris. Implikasi terhadap objek produk akta tersebut mengakibatkan dapat dibatalkan, batal demi hukum, tidak mempunyai kekuatan hukum, tidak sah atau berkekuatan hukum sebatas akta di bawah tangan. Pertanggung jawaban notaris terhadap akta yang dipalsukan maka dapat dijerat sanksi perdata, pidana, dan sanksi-sanksi lainnya.Kata kunci: notaris; autentisitas akta; pemalsuan